2009
DOI: 10.3389/neuro.07.002.2009
|View full text |Cite
|
Sign up to set email alerts
|

Early, low-level auditory-somatosensory multisensory interactions impact reaction time speed

Abstract: Several lines of research have documented early-latency non-linear response interactions between audition and touch in humans and non-human primates. That these effects have been obtained under anesthesia, passive stimulation, as well as speeded reaction time tasks would suggest that some multisensory effects are not directly influencing behavioral outcome. We investigated whether the initial non-linear neural response interactions have a direct bearing on the speed of reaction times. Electrical neuroimaging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
70
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 69 publications
(102 reference statements)
11
70
3
Order By: Relevance
“…5). This further highlights the behavioral relevance of early-latency and low-level multisensory interactions in humans (Romei et al, 2007(Romei et al, , 2009Sperdin et al, 2009Sperdin et al, , 2010Noesselt et al, 2010;Van der Burg et al, 2011) as well as monkeys (Wang et al, 2008). Such a linear relationship also provides further support to the suggestion that looming signals are on the one hand preferentially processed neurophysiologically (Maier et al, 2008) and on the other hand subject to perceptual biases (Maier et al, 2004).…”
Section: Mechanisms Subserving the Integration Of Looming Signalssupporting
confidence: 51%
“…5). This further highlights the behavioral relevance of early-latency and low-level multisensory interactions in humans (Romei et al, 2007(Romei et al, , 2009Sperdin et al, 2009Sperdin et al, , 2010Noesselt et al, 2010;Van der Burg et al, 2011) as well as monkeys (Wang et al, 2008). Such a linear relationship also provides further support to the suggestion that looming signals are on the one hand preferentially processed neurophysiologically (Maier et al, 2008) and on the other hand subject to perceptual biases (Maier et al, 2004).…”
Section: Mechanisms Subserving the Integration Of Looming Signalssupporting
confidence: 51%
“…Nonlinear ERP interactions appear to be the consequence of topographic modulations regardless of the specific type of stimuli and task. Still, it will be important to ascertain the specific mechanisms whereby task demands (Fort et al, 2002b), the sensory dominance of a given subject (Giard and Peronnet, 1999), and behavioral performance speed (Sperdin et al, 2009(Sperdin et al, , 2010) affect nonlinear neural response interactions. Subtle modulations in response profiles are consistent with what has recently been described as a "patchy" Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses here are based on the application of an additive model to detect nonlinear neural response interactions, wherein the ERP in response to the AV S condition is contrasted with the summed ERPs in response to the A S and V S conditions (hereafter referred to as "pair" and "sum" ERPs, respectively). Such a model has been repeatedly applied in ERP and magnetoencephalography studies in humans (Miniussi et al, 1998;Giard and Peronnet, 1999;Foxe et al, 2000;Murray et al, 2001Murray et al, , 2005Molholm et al, 2002;Besle et al, 2004;Möttönen et al, 2004;Brefczynski-Lewis et al, 2009;Sperdin et al, 2009Sperdin et al, , 2010Raij et al, 2010) as well as electrophysiological investigations in nonhuman primates (Meredith and Stein, 1986;Stein and Meredith, 1993;Wallace et al, 1996;Wallace and Stein, 2007;Kayser et al, 2008). Despite its widespread application, this model nonetheless receives some criticism (Gondan and Röder, 2006), which has been refuted on theoretical and empirical grounds (Fort et al, 2002a;Besle et al, 2004).…”
Section: Eeg Acquisition and Analysesmentioning
confidence: 99%
“…The notion that multisensory integration is restricted to higherorder areas has recently been challenged by human and animal studies that have revealed that crossmodal interactions can occur in unisensory areas at very low levels of cortical processing (Buchel et al, 1998;Calvert et al, 1999Calvert et al, , 2001Macaluso et al, 2000;Schroeder et al, 2001;Amedi et al, 2002;Ghazanfar et al, 2005;Kriegstein et al, 2005;Miller and D'Esposito, 2005;Watkins et al, 2006;Martuzzi et al, 2007;Kayser et al, 2007Kayser et al, , 2008Romei et al, 2007Romei et al, , 2008Wang et al, 2008) and more importantly at very short latencies (Giard and Peronnet, 1999;Foxe et al, 2000;Molholm et al, 2002;Murray et al, 2005;Senkowski et al, 2007;Sperdin et al, 2009). Such a fast timing of multisensory interactions rule out an origin in the multisensory areas mediated through backward projections, and instead favor direct heteromodal connections.…”
Section: Heteromodal Connections: Connections Between Different Sensomentioning
confidence: 99%
“…The main unanswered question is where in the brain is computed this integration that leads to an increased efficiency of the sensory-motor output. However, recent evidence points to a link between early non-linear auditorysomatosensory interactions within posterior auditory cortices with faster vs. slower RTs (Sperdin et al, 2009). …”
Section: Behavioral Evidence In the Monkeymentioning
confidence: 99%